(untitled) (An Naba, 2020)
Al-Aqsa has become an international center, a meeting place between continents in the world which has become the center of various activities, both trade, military, culture, power and others. In addition, geographically al-Aqsa has fertile land and abundant natural wealth both on land and in the sea, various fruits grow well and various livestock reproduce rapidly. The advantages possessed by al-Aqsa have resulted in a friendship for some of the nations of the world to enjoy, control and manage it. In order to thoroughly and deeply understand the various issues and conditions of al-Aqsa, the author uses a historical-religious approach as a means of proving facts and data through an analysis of the relevant verses of the Koran. This paper shows that al-Aqsa is the place of the prophets and messengers either as a place to live or as a place to stay and empirically there is no strong evidence of traces of the life of the Jewish people in Palestine that can be justified scientifically, historically and religiously.